Chinese expert consensus on diagnosis and management of acquired respiratory‐digestive tract fistulas. Issue 11 (17th September 2018) - Wang, Hongwu; Ke, Mingyao; Li, Wen; Wang, Zikai; Li, Hui; Cong, Minghua; Zeng, Yiming; Chen, Liangan; Lai, Guoxiang; Xie, Baosong; Zhang, Nan; Li, Wangping; et al.
Abstract : Acquired respiratory‐digestive tract fistulas occur with abnormal communication between the airways and digestive tract, causing the interflow of gas and liquid. Despite advances in surgical methods and the development of multimodal therapy in recent years, patients with acquired respiratory‐digestive tract fistulas continue to exhibit unfavorable clinical outcomes. Therefore, in order to guide clinical practice in China, the Respiratory and Cancer Intervention Alliance of the Beijing Health Promotion Association organized a group of experienced experts in the field to develop this consensus document. Based on a study of clinical application and expert experience in the diagnosis and management of acquired respiratory‐digestive tract fistulas at home and abroad, an Expert Consensus was developed. The panelists recruited comprised experts in pulmonology, oncology, thoracic surgery, interventional radiology, and gastroenterology. PubMed, Chinese Biology Abstract, Chinese Academic Journal, and Wanfang databases were used to identify relevant articles. The guidelines address etiology, classification, pathogenesis, diagnosis and management of acquired respiratory‐digestive tract fistulas. The statements on treatment focus on the indications for different procedures, technical aspects, and preprocedural, post‐procedural and complication management. The proposed guidelines for the diagnosis and management of acquired respiratory‐digestive tract fistulas are the first to be published by Chinese experts. These guidelines provide an in‐depth review of the current evidence and standard of diagnosis and management.